PENGARUH KONSENTRASI PEREKAT AMILUM TERHADAP KARAKTERISTIK BRIKET BIOARANG BERASAL DARI HASIL PIROLISIS LIMBAH PADAT INDUSTRI KELAPA - Lase, Winta; Purwandari, Vivi; Adiansyah; Tarigan, Malemta; Yiming, Zou (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2023)
This research is the manufacture of bio-charcoal briquettes derived from the results of pyrolysis of coconut industrial solid waste as well as an analysis of the effect of adhesive concentration on the research results of bio-charcoal briquettes. The purpose of this study was to determine the process of making bio-charcoal briquettes, the quality of the bio-charcoal briquettes and to determine the effect of the adhesive concentration used on the bio-charcoal briquettes as a result of the research. Research has been carried out on processing coconut shell and coconut coir waste with starch adhesive materials using the mixing and printing method with PVC pipes and drying in an oven with a temperature of 90–100 ºC ± 3 hours. Furthermore, the bio-charcoal briquettes were characterized based on the provisions of SNI No.01/6235/2000 which included moisture content, ash content, volatile matter content, bound carbon content, density, specific gravity, burning rate, compressive strength, calorific value with optimum values respectively 11 .46%, 3.81%, 17.60%, 77.26%, 1.2 gr/cm 3 , 1.2× 10 -6 Kg/m 2 .s 2 , 0.108 g/min, 80.680 % , 6,200 cal/g. Bio-charcoal briquettes were also tested for DTA and TGA for bio-charcoal briquettes using adhesive and without adhesive with successive values of -223.20 cal/g, -22.615%, -206.20 cal/g and -29.075%. The best quality bio-charcoal briquettes are found in briquettes with a mixture of 90% charcoal and 10% starch adhesive.